2010
DOI: 10.1111/j.1529-8817.2010.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in Isomorphic Phase and Sex Ratios of a Natural Population of Ulva Pertusa (Chlorophyta)1

Abstract: The green macroalga Ulva L. is well known as having an alternation of isomorphic biphases: gametophyte and sporophyte. However, an examination of the temporal alternation in phase dominance has not been carried out. By inducing reproduction of thallus samples in the laboratory, this study reports the temporal changes in the two phases and sex ratios in a natural population of Ulva pertusa Kjellm. in the Seto Inland Sea, Japan, over a period of >3 years. The results showed that a temporal alternation in phase d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…High variability of microbial communities from the same host has been shown for several other macroalgal species (Miranda, Hutchison, Grossman, & Brawley, 2013;Stratil, Neulinger, Knecht, Friedrichs, & Wahl, 2013). Such within-species variation would further support the hypothesis of horizontal acquisition of the epiphytic microbiota and may reflect seasonal variation of bacterial communities in the surrounding seawater (Schauer, Balagu e, & Pedr os-Ali o, 2003) or the fact that the reproduction of Ulva occurs in different seasons (Hiraoka & Yoshida, 2010). However, for the current study, individual thalli of the same size were sampled and thus should be coetaneous.…”
Section: Specificity Of Bacterial Communities On Cooccurring Ulva Ssupporting
confidence: 70%
“…High variability of microbial communities from the same host has been shown for several other macroalgal species (Miranda, Hutchison, Grossman, & Brawley, 2013;Stratil, Neulinger, Knecht, Friedrichs, & Wahl, 2013). Such within-species variation would further support the hypothesis of horizontal acquisition of the epiphytic microbiota and may reflect seasonal variation of bacterial communities in the surrounding seawater (Schauer, Balagu e, & Pedr os-Ali o, 2003) or the fact that the reproduction of Ulva occurs in different seasons (Hiraoka & Yoshida, 2010). However, for the current study, individual thalli of the same size were sampled and thus should be coetaneous.…”
Section: Specificity Of Bacterial Communities On Cooccurring Ulva Ssupporting
confidence: 70%
“…However, this requires confirmation through the cultivation of successive generations. In general, gametes are positively phototactic [34], [67], [68], while asexual biflagellate zoids are negatively phototactic [17], as are quadriflagellate zoospores [37] and zygotes [34]. The negative phototaxis guides swarmers to suitable surfaces for settlement and attachment [69].…”
Section: Discussionmentioning
confidence: 99%
“…The green macroalgal genus Ulva forms large and dense sheets, a phenomenon known as green tides, and can proliferate by asexual (e.g., fragmentation, spore formation) [ 5 , 17 , 18 ] and sexual reproduction [ 19 ]. Green tides include many genera of green algae, such as Chaetomorpha , and affect at least 37 countries worldwide [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are few published studies on the in situ life cycle dynamics of Ulva ; Hiraoka and Yoshida [ 19 ] found a non-seasonal alternating dominance of the two phases for U . pertusa , Alström-Rapaport and colleagues [ 24 ] and Pringle [ 25 ] found a seasonal shift, with an increase of the proportion of gametophytes during the summer months in U .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation